Research of medical treatment influence of "melanizol" suppositories on background of "mechanical" vaginitis in rats - Dolzhykova, Olena; Maloshtan, Ludmila (ScienceRise: Pharmaceutical Science, 2020)
The aim. To study the therapeutic effect of new vaginal suppositories "Melanizol" based on metronidazole and tea tree oil on a model of "mechanical" vaginitis in female rats. Methods. The therapeutic effect of suppositories of "Melanizol" has been studied in female rats on the model of "mechanical" vaginitis, which is a secondary insemination of vaginal. On the background of vaginitis the general condition of the animals, the dynamics of body weight, the morphological composition of peripheral blood, the rate of erythrocyte sedimentation, changes in pH and temperature in the vagina were examined, and macroscopic evaluation of vaginal mucosa was evaluated. Results. The results of studies show that, on the background of pathology, there were shifts that were manifested by a clear swelling of the tissues around the vagina, a decrease in body weight, a shift in the pH to the alkaline side, an increase in the temperature in the vagina, leukocytosis, a shift of the leukocyte formula toward an increase in the number of neutrophils, increasing the erythrocyte sedimentation rate. In the vaginal mucosa were observed lesions, manifested by edema, hyperemia, and numerous hemorrhages. Under conditions of treatment with suppositories "Melanizol" a reliable restoration of the pH and decrease in the temperature of the vagina of animals, a decrease in the rate of sedimentation of erythrocytes, the total number of leukocytes and the restoration of the level of neutrophils to indicators of the group of intact animals were observed. Macroscopic studies of the vaginal mucosa showed a therapeutic effect of vaginal suppositories "Melanizol", it was manifested by a significant reduction in the area of the affected area of the vagina and its manifestations. The effectiveness of the suppositories of "Melanizol" significantly surpassed the comparison drug of "Gravagin" and were practically of the same efficiency as the reference drug "Hippophaes oleum suppositories". Conclusions. The therapeutic effect of new vaginal suppositories of "Melanizol" based on metronidazole and tea tree oil on the model of "mechanical" vaginitis in female rats has been proved. Studied suppositories "Melanizol" is a perspective drug for the treatment of non-specific vaginitis caused by mechanical irritants and need further research in this direction.